2020
DOI: 10.1177/2192568220975378
|View full text |Cite
|
Sign up to set email alerts
|

Redundant Nerve Roots of the Cauda Equina, MRI Findings and Postoperative Clinical Outcome: Emphasizing an Overlooked Entity

Abstract: Study Design: Retrospective study. Objective: To describe the MRI findings of RNRs in patients with low back pain, and observe the imaging findings and the clinical outcome post decompression surgery. Methods: The lumbar spine MRI of 202 patients (122 females) with proven RNRs were retrospectively reviewed. The morphology and the location of the RNRs in relation to the level of stenosis were described. The level(s), grade and cause of lumbar canal stenosis were recorded. The persistence of symptoms and the ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
1
7
1
Order By: Relevance
“…This result is also consistent with the findings reported by Nathani et al. 11 , 18 It may be assumed that more degenerative changes of the spine occur over time, resulting in the development of RNRS. Among the MRI parameters, the dural sac AP diameter, left ligamentum flavum thickness, and right foraminal AP diameter were significantly correlated with RNRS.…”
Section: Discussionsupporting
confidence: 93%
“…This result is also consistent with the findings reported by Nathani et al. 11 , 18 It may be assumed that more degenerative changes of the spine occur over time, resulting in the development of RNRS. Among the MRI parameters, the dural sac AP diameter, left ligamentum flavum thickness, and right foraminal AP diameter were significantly correlated with RNRS.…”
Section: Discussionsupporting
confidence: 93%
“…The difference in our study may be attributed to initial selection bias caused by inclusion of patients who underwent an EDX study for several reasons, primarily severe neurological symptoms. Neurogenic symptoms were more prevalent in our study than in the prior study, 3 even in the non-RNR group.…”
Section: Discussioncontrasting
confidence: 71%
“…As RNRs were initially described by myelographic findings, they were mainly classified by their morphology as serpentine or loop type. Several studies have explored the clinical significance of RNR morphology 3,6,12,22 . Yokoyama et al, 22 who followed up 33 patients with LSS who had RNRs for 1 year after decompression laminectomy, reported that loop‐type RNRs were more frequent in patients with poorer functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations